Descrição fonética e fonológica do pomerano falado no Espírito Santo - Schaeffer, Shirlei Conceição Barth (2012)
Since 1859 the state of Espirito Santo received immigrants from the extinct Pomeranian, which included parts of current Germany and Poland. Initially, they went to Santa Leopoldina Colony. Nowadays, the descendants of Pomeranians are concentrated in fourteen places in Espirito Santo forming a contiguous area on the mountainous regions to the north of the state (TRESSMANN, 2005). These descendants still preserve Pomeranian cultural characteristics and the language of their ancestors, so that many descendants learn the Portuguese language at school. Although the Pomeranian language is widely spoken in different places of the state, it does not have a satisfactory linguistic description. Thus, there is interest in describing the phonetic system of this language, so as to understand its sound structure and then make inferences about possible transfer processes of phonetic features from Pomeranian to Portuguese in bilingual speakers. To carrying out this research, we have adopted Pike’s phonemic model (1947). The corpus consisted of 600 words spoken by four speakers (one man and three women), who have the Pomeranian as their mother tongue and are residents in Santa Leopoldina-ES. The consonantal and the vocalic phones were distributed in a phonetic table according to their articulatory description. Then, the phonemes were defined and an analysis of the syllabic structure was made. Finally, an acoustic analysis of the Pomeranian stop consonants was made. Based on these analyses, we concluded that this language has 18 consonantal phonemes and 13 vocalic phonemes. Besides, the voiceless stops are aspirated and the voiced stops have a VOT mean close to the Brazilian Portuguese voiceless stops.